2004
DOI: 10.1007/bf03027357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of be addition on the oxidation behavior of Mg−Ca alloys at elevated temperature

Abstract: Beryllium was added to Mg-Ca alloys to study their ignition-proof properties. The ignition temperatures of Mg-2Ca alloys were increased dramatically with increasing Be addition. Thermogravimetric measurement revealed that the oxidation of Mg-2Ca alloys was slowed down by Be addition. After elevated temperature exposure to air, the Mg-2Ca alloy was partially ignited, while the surface of Be-containing alloys was smooth without any partial ignition. SEM, low-angle XRD, and AES observations indicated that the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 8 publications
0
10
1
1
Order By: Relevance
“…In the case of Be, even though the solute solubility of Be in Mg is almost zero [169], a Mg-0.15Be alloy exhibits an ignition temperature of 750 C [198]. Furthermore, microalloying of Mg-Ca alloy with Be produced a significantly higher ignition temperature of 1050 C [165] as shown in Table 2.…”
Section: Discussion On Ignition Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…In the case of Be, even though the solute solubility of Be in Mg is almost zero [169], a Mg-0.15Be alloy exhibits an ignition temperature of 750 C [198]. Furthermore, microalloying of Mg-Ca alloy with Be produced a significantly higher ignition temperature of 1050 C [165] as shown in Table 2.…”
Section: Discussion On Ignition Temperaturementioning
confidence: 99%
“…Because of the high P-B ratio of BeO (1.70) [62], the BeO film was considered a barrier to prevent oxygen penetration. Huang et al [165] reported an increase of 200 C in the ignition temperature of a Mg-2Ca alloy after alloying with 300 ppm (wt) Be. Zeng et al [166,167] reported that 0.3 wt.% Be-containing AZB910 could be melted without burning, even without a shielding gas.…”
Section: Bementioning
confidence: 99%
“…In the case of Be, even though the solute solubility of Be in Mg is almost zero [169], a Mg-0.15Be alloy exhibits an ignition temperature of 750 C [198]. Furthermore, microalloying of Mg-Ca alloy with Be produced a significantly higher ignition temperature of 1050 C [165] as shown in Table 2. Based on the analogy with Sr, the excellent ignition resistance by micro-alloying with Be may also be attributed to a surface active effect.…”
Section: Discussion On Ignition Temperaturementioning
confidence: 99%
“…Because of the high P-B ratio of BeO (1.70) [62], the BeO film was considered a barrier to prevent oxygen penetration. Huang et al [165] reported an increase of 200 C in the ignition temperature of a Mg-2Ca alloy after alloying with 300 ppm (wt) Be. Zeng et al [166,167] reported that 0.3 wt.% Becontaining AZB910 could be melted without burning, even without a shielding gas.…”
Section: Bementioning
confidence: 99%
See 1 more Smart Citation